Good God but You Smart! : Language Prejudice and Upwardly Mobile Cajuns - Stanford, Nichole, 1977- (Book collections on Project MUSE., 2016)
"First comprehensive book in Composition Studies to examine educational and linguistic assimilation, as well as the local languages--Louisiana French and prevalent Cajun English--of Cajuns and explores the subtle ways grammar snobbery, from classrooms to families to pop culture references, is used to justify systemic inequality"--Provided by publisher.